2021
DOI: 10.3389/fpls.2021.645671
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nitrate Content in Baby-Leaf Lettuce and Cichorium endivia Through the Soilless Cultivation System, Electrical Conductivity and Management of Nutrient Solution

Abstract: Soilless cultivation systems are efficient tools to control nitrates by managing nutrient solution (NS) salinity and nitrogen availability, however, these nitrate-lowering strategies require appropriate calibration based on species/genotype-specific responses interacting with climate and growing conditions. Three experiments were carried out on lettuce and Cichorium endivia grown in ebb-and-flow (EF) and floating (FL) systems at two levels of NS salinity (EC = 2.5 and 3.5 dS m−1) (EC2.5, EC3.5, respectively) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“… Rouphael et al (2019) obtained a decrease in accumulation of NO 3 – in leaves of green and red-pigmented perilla by applying a 10 mM NaCl eustress, and at the same time, this treatment enhanced polyphenols and therefore the antioxidant activity. Lettuce plants underwent a decrease in the leaf NO 3 – content between 20 and 35 mM NaCl, which determined an increase in polyphenols but also a decrease in the growth and yield proportional to the increase in the salinity ( Carillo et al, 2020 , 2021 ; Conversa et al, 2021 ). However, Conversa et al (2021) found that the endive plants showed a decrease in the antinutrient nitrate without a simultaneous effect on the yield even at 35 mM NaCl (3.5 dS m –1 ), probably due to the higher salt tolerance of this plant.…”
Section: Nitrate Accumulation and Chloride Eustressmentioning
confidence: 99%
“… Rouphael et al (2019) obtained a decrease in accumulation of NO 3 – in leaves of green and red-pigmented perilla by applying a 10 mM NaCl eustress, and at the same time, this treatment enhanced polyphenols and therefore the antioxidant activity. Lettuce plants underwent a decrease in the leaf NO 3 – content between 20 and 35 mM NaCl, which determined an increase in polyphenols but also a decrease in the growth and yield proportional to the increase in the salinity ( Carillo et al, 2020 , 2021 ; Conversa et al, 2021 ). However, Conversa et al (2021) found that the endive plants showed a decrease in the antinutrient nitrate without a simultaneous effect on the yield even at 35 mM NaCl (3.5 dS m –1 ), probably due to the higher salt tolerance of this plant.…”
Section: Nitrate Accumulation and Chloride Eustressmentioning
confidence: 99%
“…Savvas and Gruda [10] and Gruda et al [59] also reported some methods to reduce the nitrate contents in SCS-leafy vegetables by lowering or eliminating the NO 3 -N supply a few days before harvesting. However, nitrate-lowering strategies require appropriate calibration based on species-/genotype-specific responses interacting with climate and growing conditions [60].…”
Section: Nutrient Solutionmentioning
confidence: 99%
“…NO 3 concentration in leaf vegetables can be manipulated by reducing or withdrawing NO 3 supply prior to harvesting (He et al, 2011a(He et al, , 2014Conversa et al, 2021). In this study, all M. crystallinum plants were first grown with full N for 11 days before transferring them to 3/4 N, 1/2 N, 1/4 N, and 0 N conditions for another 7 days.…”
Section: Productivity Of Shoot and Root And Leaf Growthmentioning
confidence: 99%
“…Reduced NO 3 availability in the growth media results in reduced accumulation of NO 3 in edible portions of crop plants (He et al, 2014;Bian et al, 2020;Conversa et al, 2021). However, in the present study, compared with M. crystallinum plants grown with full N, those transferred from full N to 3/4 N, 1/2 N, and 1/4 N seemed to be constant or slightly increased in shoot NO 3 concentrations during the reduced NO 3 treatments on a DW (Figure 4A) or a FW basis (Figure 4B).…”
Section: Shoot No 3 -Concentrations Nra and Leaf Total Soluble Proteinmentioning
confidence: 99%
See 1 more Smart Citation